KETERLIBATAN MASYARAKAT PEDESAAN TERHADAP PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PERUSAHAAN - Widhy Andrian Pratama Widh (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2026)
Corporate responsibility can be realized through various activities oriented towards community empowerment and environmental preservation. The forms of implementation include improving the quality of life of the community, environmental protection, providing educational assistance in the form of scholarships for underprivileged children, financial support for the maintenance of public facilities, as well as other contributions to village development and the provision of social facilities that benefit the wider community. This Community Service activity is a manifestation of the implementation of the Tridharma of Higher Education carried out by lecturers of the Department of Law, Faculty of Law, Syekh Yusuf Al-Makassari University, Gowa, in collaboration with PT. Indo Mineral Mining. The synergy aims to ensure that the Corporate Social Responsibility (CSR) program is implemented effectively, transparently, accountably, and sustainably. This activity was carried out on Thursday, January 13, 2026, in Tanakuraya Village, North Bungku District, North Morowali Regency, Central Sulawesi Province. The results of the activity show that CSR has a significant role in creating a harmonious relationship between companies and the community. Through a series of outreach activities, discussions, and training, the community gained a better understanding of their rights and obligations as stakeholders, including in the application, implementation, and oversight of CSR programs. Furthermore, through Focus Group Discussions (FGDs) and direct communication with residents, several key community needs were identified, including the provision of clean water, strengthening community economic capacity, and improving the quality of education.